Report of the FAO expert workshop on climate change implications for fisheries and aquaculture : (Food and Agriculture Organization of the United Nations, 2008)
This Expert Workshop was convened to identify and review the key issues of climate change in relation to fisheries and aquaculture, from the physical changes, the impacts of those on aquatic resources and ecosystems and how these ecological impacts translate into human dimensions of coping and adapting within fisheries and aquaculture. The workshop also evaluated policy options and activities at the international, regional and national levels that can help minimize negative impacts of climate change, improve on mitigation and prevention, and maintain and build adaptive capacity to climate change.